The effect of ubiquinone and combined antioxidant therapy on oxidative stress markers in non-proliferative diabetic retinopathy: A phase IIa, randomized, double-blind, and placebo-controlled study - Adolfo Daniel Rodríguez-Carrizalez; José Alberto Castellanos-González; Esaú César Martínez-Romero; Guillermo Miller-Arrevillaga; Fermín Paul Pacheco-Moisés; Luis Miguel Román-Pintos; Alejandra Guillermina Miranda-Díaz (Redox Report)
Objective To evaluate the effect of ubiquinone (Coenzyme Q10) and combined antioxidant therapy (CAT) on oxidative stress markers in non-proliferative diabetic retinopathy (NPDR) under clinical management.Study design In a randomized, double-blind, phase IIa, placebo-controlled, clinical trial, three study groups were formed and administered medications as follows: Group 1, Coenzyme Q10; Group 2, CAT; and Group 3, placebo.Methods Serum levels of the products of lipid peroxidation (LPO) and nitrites/nitrates, as markers of oxidative/nitrosative stress, were measured. As antioxidants, the total antioxidant capacity (TAC), catalase activity, and glutathione peroxidase (GPx) activity were measured.Results Baseline serum levels of LPO and nitrites/nitrates were significantly elevated in the three groups vs. healthy group (P < 0.0001), while final levels in the Coenzyme Q10 and CAT groups were decreased vs. normal levels (P < 0.0001). The baseline TAC was consumed in the three groups (P < 0.0001), while final results in the Coenzyme Q10 and CAT groups improved (P < 0.0001). Baseline catalase activity was increased in all groups vs. normal values (P < 0.001), while final levels in the Coenzyme Q10 (P < 0.001) and CAT groups (P < 0.0001) were decreased. GPx behaved similarly to catalase and improved in the final results (P < 0.0001).Discussion Adjunctive antioxidant treatment for 6 months was effective and safe for improving the oxidative stress in NPDR.